Factors That Support The Completeness of Filling Out KIA Book (Mother and Child Health) - Ustriyaningsih, Ustriyaningsih; Irene Kartasurya, Martha; Sriatmi, Ayun (Green Publisher Indonesia, 2022)
The KIA Handbook is a manual that contains information sheets and records of health services for mothers and children. However, the use of the KIA handbook has not achieved maximum results because the documentation system is still done conventionally. This study aims to analyze and describe the input, planning, and organizing factors that affect the completeness of filling out the KIA handbook. This study uses a literature review method. Journal searches were obtained from the Google Scholar database using keywords and inclusion criteria. The steps of data analysis are: data collection, data reduction, data presentation, and conclusions. The article search results obtained 34 articles published in national online journals using the Google Scholar search engine with keywords and inclusion criteria, namely: time period, language, subject, type of article, and theme of article content. The conclusions in this study are: (1) The input factors that affect the completeness of filling out the KIA book from the midwife's side are knowledge, attitudes, skills, while from the mother's side, namely in terms of knowledge, (2) Planning factors that affect the completeness of filling out the KIA book are service SOPs. Antenatal care at the Puskesmas is made by the Puskesmas based on the integrated antenatal service guidelines set by the District Health Office, and (3) Organizing factors that affect the completeness of filling out the KIA handbook, namely cooperation and joint commitment by each part involved such as: Health Office, Head of Puskesmas, Implementing Midwives, Local Government (Districts), Pregnant Women's Families, and Employers